J. Roney Ranch in Sunol - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Panoramic landscape of orchards situated among grass fields and shrub land. To the far left, a farm outbuilding and wind mill is partially visible. To the far right, a series of high voltage towers and electric lines can be seen in the distant hills.